Versatile Sequential Casting Processing for Highly Efficient and Stable Binary Organic Photovoltaics (Adv. Mater. 33/2022). Issue 33 (18th August 2022) - He, Chengliang; Pan, Youwen; Lu, Guanghao; Wu, Baohua; Xia, Xinxin; Ma, Chang‐Qi; Chen, Zeng; Zhu, Haiming; Lu, Xinhui; Ma, Wei; Zuo, Lijian; Chen, Hongzheng
Abstract : Organic Solar Cells Forming an ideal bulk heterojunction morphology is a critical issue governing the photon to electron process in organic solar cells (OSCs). In article number 2203379, Lijian Zuo, Hongzheng Chen, and co‐workers show how sequential‐casting (SC) processing is practical and universal for improvement of device performance in both fullerene‐ and nonfullerene‐based systems, in which the donor and acceptor are deposited sequentially. The fabricated OSCs show advantages regarding device performance, photostability and upscale fabrication. Such a film spin‐coating method is analogous to the traditional Chinese pancake making process.